Construtivismo e métodos tradicionais: uma análise dos processos de alfabetização atuais - Silva, Bruna Gonçalves da; Martins, Maria Angélica Seabra Rodrigues [UNESP] (My University, 2012)
This paper intended to observe the alphabetization process in Brazil, looking for the constructivist model and its difficulties also observing the phonic and the syllabic methods in order to consider the adaptations of these methods for the children’s learning writing language. Without choose between one method in particular this article purposes to do a study of the difficulties that the children shows during the learning of the lecture and writing, in order to help the teachers to think about the problems found and how they may obtain solutions for them when they are in the front of a different group of students.

Pretendeu-se neste artigo observar o processo de alfabetização no país, a partir do modelo construtivista, e suas dificuldades, observando-se também o método fônico e silábico, com o objetivo de refletir acerca das adequações desses modelos para a aprendizagem da linguagem escrita pelas crianças. Sem optar por um método ou por outro, este estudo visa a fazer um estudo das dificuldades apresentadas pelos alunos, quanto à aprendizagem da leitura e da escrita, auxiliando o professor a refletir sobre muitos dos problemas encontrados e a obter soluções para os mesmos, diante de clientela variada.
Keywords: Alphabetization; Phonics; Syllabics; Constructivism; Alfabetização; Fonética; Silabação; Construtivismo